A study of the dynamics of quantum correlations - Camati, Patrice Audibert [UNESP] (2014)
In this work, we present an introduction to the quantum information theory. Before dealing with quantum information we develop some necessary tools, the classical information theory and some important concepts in quantum dynamics. We de?ne measures of quantum correlations, concurrence and quantum discord, and study their dynamical evolution when the coupling between the system and environment is considered random. We conclude that a random environment imposes permanent loss of correlations to the system